Poor Performance of Serological Tests in the Diagnosis of Pulmonary Tuberculosis: Evidence from a Contact Tracing Field Study - Singh, Sarman (Public Library of Science, 2012)
BACKGROUND: Delayed or missed diagnosis of TB continues to fuel the global TB epidemic, especially in resource limited settings. Use of serology for the diagnosis of tuberculosis, commonly used in India, is another factor. In the present study a commercially available serodiagnostic assay was assessed for its diagnostic value in combination with smear, culture and clinical manifestations. METHODOLOGY/PRINCIPAL FINDINGS: A total of 2300 subjects were recruited for the study, but 1041 subjects were excluded for various reasons. Thus 1259 subjects were included in the study of which 470 were pulmonary tuberculosis cases (440 of 470 were culture-positive) and 789 were their asymptomatic contacts. A house-to-house survey method was used. Blood samples were tested for IgM, IgA, and IgG antibodies using the Pathozyme Myco M (IgM), Myco A (IgA) and Myco G (IgG) enzyme immunoassay (EIA). Out of 470 PTB cases, BCG scar was positive in 82.34%. The Mantoux test and smear positivity rates in PTB cases were 94.3% (430/456), and 65.32% (307/470), respectively. Among the asymptomatic contacts, BCG scar was positive in 95.3% and Mantoux test was positive in 80.66% (442/548) contacts. No contact was found falsely smear positive. The sensitivity of IgM, IgA, and IgG EIA tests was 48.7%, 25.7% and 24.4%, respectively, while the specificity was 71.5%, 80.5%, 76.6%, respectively. Performance of EIAs was not affected by the previous BCG vaccination. However, prior BCG vaccination was statistically significantly (p = 0.005) associated with Mantoux test positivity in PTB cases but not in contacts (p = 0.127). The agreement between serology and Mantoux test was not significant. CONCLUSION: The commercial serological test evaluated showed poor sensitivity and specificity and suggests no utility for detection of pulmonary tuberculosis.